Recombinant GM-CSF for diseases of GM-CSF insufficiency: Correcting dysfunctional mononuclear phagocyte disorders - Lazarus, Hillard M.; Pitts, Katherine; Wang, Tisha; Lee, Elinor; Buchbinder, Elizabeth; Dougan, Michael; Armstrong, David G.; Paine, Robert; Ragsdale, Carolyn E.; Boyd, Timothy; Rock, Edwin P.; Gale, Robert Peter (Frontiers in Immunology, 2023)
Introduction Endogenous granulocyte-macrophage colony-stimulating factor (GM-CSF), identified by its ability to support differentiation of hematopoietic cells into several types of myeloid cells, is now known to support maturation and maintain the metabolic capacity of mononuclear phagocytes including monocytes, macrophages, and dendritic cells. These cells sense and attack potential pathogens, present antigens to adaptive immune cells, and recruit other immune cells. Recombinant human (rhu) GM-CSF (e.g., sargramostim [glycosylated, yeast-derived rhu GM-CSF]) has immune modulating properties and can restore the normal function of mononuclear phagocytes rendered dysfunctional by deficient or insufficient endogenous GM-CSF. Methods We reviewed the emerging biologic and cellular effects of GM-CSF. Experts in clinical disease areas caused by deficient or insufficient endogenous GM-CSF examined the role of GM-CSF in mononuclear phagocyte disorders including autoimmune pulmonary alveolar proteinosis (aPAP), diverse infections (including COVID-19), wound healing, and anti-cancer immune checkpoint inhibitor therapy. Results We discuss emerging data for GM-CSF biology including the positive effects on mitochondrial function and cell metabolism, augmentation of phagocytosis and efferocytosis, and immune cell modulation. We further address how giving exogenous rhu GM-CSF may control or treat mononuclear phagocyte dysfunction disorders caused or exacerbated by GM-CSF deficiency or insufficiency. We discuss how rhu GM-CSF may augment the anti-cancer effects of immune checkpoint inhibitor immunotherapy as well as ameliorate immune-related adverse events. Discussion We identify research gaps, opportunities, and the concept that rhu GM-CSF, by supporting and restoring the metabolic capacity and function of mononuclear phagocytes, can have significant therapeutic effects. rhu GM-CSF (e.g., sargramostim) might ameliorate multiple diseases of GM-CSF deficiency or insufficiency and address a high unmet medical need.